Study Abroad Programs: A Mirror for Adult Learning and Perspective Transformation - Kathryn A. Sanders; Marilon Morgan (Adult Education Research Conference, 2001)
This pilot study qualitatively sought to examine how study abroad programs in Third-World countries provide a means of fostering perspective transformation in adult learners. A diverse group of students and faculty from four cooperating universities participated in a six-week study abroad program in Africa. It examined the concepts of perspective transformation, transformative learning, and critical reflection.